The Effect of Capital Intensity and Thin Capitalization on Tax Avoidance with Company Size as a Moderator - Heriyanti, I Dewa Ayu; Pradana Adiputra, I Made; Sri Musmini, Lucy (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Tax avoidance refers to efforts undertaken by taxpayers to legally minimize tax burdens by exploiting loopholes or weaknesses within existing tax regulations. Several factors may contribute to tax avoidance practices, including capital intensity, thin capitalization, and firm size. This study aims to analyze the effects of capital intensity and thin capitalization on tax avoidance, with firm size serving as a moderating variable, in property and real estate sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The research employs a quantitative approach using multiple linear regression analysis and moderated regression analysis, with data processed through Stata. The sampling technique applied was purposive sampling, resulting in 180 observations derived from 45 companies. The findings indicate that capital intensity has a significant effect on tax avoidance, whereas thin capitalization does not significantly affect tax avoidance. Furthermore, firm size is proven to moderate the influence of both capital intensity and thin capitalization on tax avoidance. These findings suggest that the scale of a company may influence its tendency to utilize debt financing and fixed asset ownership as mechanisms for tax management.